2021
DOI: 10.1103/physrevlett.127.220501
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Detection of High-Dimensional Entanglement

Abstract: Entanglement detection is one of the most conventional tasks in quantum information processing. While most experimental demonstrations of high-dimensional entanglement rely on fidelity-based witnesses, these are powerless to detect entanglement within a large class of entangled quantum states, the so-called unfaithful states. In this paper, we introduce a highly flexible automated method to construct optimal tests for entanglement detection given a bipartite target state of arbitrary dimension, faithful or unf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Zhang et al explored the multipartite entanglement in an optical lattice [8]. Hu et al realized the optimal detection of highdimensional entanglement, and their method is applicable to bipartite state of arbitrary dimension [9]. The genuinely multipartite entanglement with general and Robust device-independent were verified by Zhang et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al explored the multipartite entanglement in an optical lattice [8]. Hu et al realized the optimal detection of highdimensional entanglement, and their method is applicable to bipartite state of arbitrary dimension [9]. The genuinely multipartite entanglement with general and Robust device-independent were verified by Zhang et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…As the faithful sates are equivalent to the states with f > 1/d, faithfulness of entanglement can be enhanced by this class of channel. Recently, faithfulness of entanglement was studied by experiments [7,20]. The authors demonstrated a situation in which an unfaithful state is brought to a faithful one in the amplitude damping channel [7].…”
Section: Introductionmentioning
confidence: 99%